Strontium-doped hardystonite plasma sprayed coatings with robust antimicrobial activity. (June 2022) - Pham, D.Q.; Gangadoo, S.; Lu, Z.; Berndt, C.C.; Newsom, E.T.; Zreiqat, H.; Truong, V.K.; Ang, A.S.M.
Abstract: A strontium-doped hardystonite (Sr-HT) bioceramic, in bulk form, demonstrates excellent bioactivity for bone regeneration with high fracture toughness and compressive strength. This work examines the antibacterial and mechanical properties of Sr-HT coatings on an alpha-beta titanium alloy with a high specific strength and excellent corrosion resistance (Ti-6Al-4V) produced by atmospheric plasma spray (APS) as the deposition coating technique. A hydroxyapatite (HAp) APS coating, a commercial bioceramic coating, is chosen as the control. The in-situ observation showed that Sr-HT powders experience temperatures during plasma processing that exceeded their melting point to form a coating well adhered to the substrate. It was demonstrated that the Sr-HT coating possessed superior antibacterial properties against Gram-positive methicillin-resistant Staphylococcus aureus (MRSA) and Gram-negative Pseudomonas aeruginosa . In addition, the Sr-HT coating exhibits a uniform distribution of hardness and elastic moduli, higher nanohardness and elastic moduli compared to the equivalent properties of the HAp coating. Moreover, the Sr-HT coating outperforms the HAp coating regarding scratch and wear resistance. The bonding and shear strength of the Sr-HT coating are higher than the values required for orthopedic implant coatings. The Sr-HT coating also allows efficient zinc, silicon and strontium ions release when immersed in cell culture media. In summary, the antibacterial capabilities and the mechanical properties of the Sr-HT APS coating exceed those of the commercial HAp APS coating. Therefore, Sr-HT APS coatings are candidates for bioceramic coating applications in orthopedic implants. Graphical abstract: Image 1 Highlights: Sr-HT coating produced with APS presented improvements in mechanical properties. Sr-HT coating exhibited a higher and more homogeneous elastic modulus and hardness. Sr-HT coating exhibited better local scratch and wear resistance compared to HAp. Under static tensile and static shear tests, the Sr-HT outperformed HAp coatings. Sr-HT coating show antibacterial properties against MRSA and P. aeruginosa strains.